2005
DOI: 10.1038/sj.bjc.6602741
|View full text |Cite
|
Sign up to set email alerts
|

Oncofoetal fibronectin – a tumour-specific marker in detecting minimal residual disease in differentiated thyroid carcinoma

Abstract: Supposedly, thyrocyte-specific transcripts such as thyroglobulin (Tg) and thyroid-stimulating hormone receptor (TSH-R) were proposed to be useful for the diagnosis of circulating tumour cells in patients suffering from differentiated thyroid carcinoma (DTC). However, several research groups reported blood-borne Tg transcripts in healthy individuals. This study determines in particular the origin of Tg mRNA in nucleated blood cells and analyses whether other tumour-associated sequences are absent in leukocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Copy numbers were normalized to porphobilinogen desaminase, and results were expressed as arbitrary units. All procedures have been described previously in all details (12).…”
Section: Quantification Of Onffn Mrnamentioning
confidence: 99%
See 1 more Smart Citation
“…Copy numbers were normalized to porphobilinogen desaminase, and results were expressed as arbitrary units. All procedures have been described previously in all details (12).…”
Section: Quantification Of Onffn Mrnamentioning
confidence: 99%
“…2,[9][10][11]. A recent report from our group has described a highly sensitive assay to quantify oncofetal fibronectin (onfFN) mRNA in the peripheral blood of patients with DTC metastatic disease (12). As discussed later, we consider that onfFN mRNA in peripheral blood is probably derived from circulating rather than tissue cells.…”
Section: Introductionmentioning
confidence: 95%
“…Also, there were only 4 FTC out of 21 patients (19.0%) in the disease groups and 7 out of 30 (23.3%) in the disease-free group, therefore, the inclusion proportion of patients with FTC should not account for this indifference. In fact, Hesse et al (Hesse et al, 2005) showed that detectable levels of onfFN were found in the majority of the tissue samples of FTC but only 11% having high expression. Also, a quarter of all PTC tumours only displayed intermediate and low (13%) onfFN signals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the use of OnfFN mRNA in identifying metastatic DTC by Hesse et al (Hesse et al, 2005), we applied to assess if the onfFN mRNA in the peripheral blood of the patients with metastatic DTC can be used to differentiate between the active and disease-free groups. Generally, the patients were considered disease-free after total thyroidectomy and radioiodine ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation